2010
DOI: 10.1007/s00280-010-1450-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of erlotinib as first-line treatment for Asian elderly patients with advanced non-small-cell lung cancer

Abstract: The results suggest that erlotinib monotherapy is an effective and well-tolerated treatment option for Asian elderly patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Studies that focused on efficacy of erlotinib after gefitinib failure were excluded. The results are summarized in Supplementary Table 2 [11][12][13]27,28]. We found 5 studies with total 81 patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies that focused on efficacy of erlotinib after gefitinib failure were excluded. The results are summarized in Supplementary Table 2 [11][12][13]27,28]. We found 5 studies with total 81 patients.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies independently observed the objective responses of erlotinib in lung SCC patients [11][12][13]. However, the real efficacy of erlotinib in these patients remains unclear due to limited case numbers of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…It emphasizes the importance of risk assessment of tumor progression in these patients, and CTCs are considered as the predictive biomarker for guiding cancer treatment strategies [25]. CTCs count was proved to predict the radiation therapy response of NSCLC patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targeted therapies have advanced most for younger patients with LUAD, who are mostly neversmokers. Recently, EGFR-TKI has emerged as an alternative treatment option for advanced NSCLC [7][8][9]. ese findings suggest that erlotinib monotherapy is an effective and well-tolerated treatment option for elderly Asian patients with advanced NSCLC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, EGFR-TKI has emerged as an alternative treatment option for advanced NSCLC [7][8][9]. ese findings suggest that erlotinib monotherapy is an effective and well-tolerated treatment option for elderly Asian patients with advanced NSCLC [7]. Moreover, in patients suffering from advanced NSCLC, bevacizumab improved the overall survival when paclitaxel-carboplatin was added [10].…”
Section: Introductionmentioning
confidence: 99%